PENERAPAN IPTEK PADA USAHA KECIL ROTI BAKAR - Khumaedi, Muhammad; Eko, Budiarso; Rusiyanto, Rusiyanto (Universitas Negeri Semarang, 2017)
The target of this devotion is to make the enterprise of toast bread “Maju Terus Jaya” helps making the milling machine of toast bread dough that has quality. And for the “Ivan” toast bread enterprise is uploading the advertisement on the internet in order to be better known by the so- ciety surrounding Sampangan, Semarang and making the packaging of toast bread wrapper. Method to resolve the problem is using several ways that supporting one and the others and adapted with the steps that will be done. The steps of the method as follows: counseling, demonstrations, train- ing, making an advertisement and mentoring. The results of this activity to the enterprise of toast bread “MajuTerus Jaya” is the manufacture of a dough milling machine that produces qualified toast bread with the inside structure that more subtle, chewy, and soft. And for the enterprise of toast bread “Ivan” has been successfully created an advertisement that is uploaded on the internet and making the packaging of toast bread wrapper more attractive. The impact of the results of activity that done is the production of toast bread that is sold being able to increase so that the net profit of the enterprise of toast bread “Maju Terus Jaya” and the selling of toast bread “Ivan” increases